Pains of privacy: Mapping carceral practices onto electronic monitoring - Kirk-Werner, Gabriela (Theoretical criminology, 2025)
Scholars and policymakers have long debated whether electronic monitoring programs can be understood as a carceral experience. Recent changes to the technology that utilize 24/7 location monitoring through GPS are changing the nature of electronic monitoring. Given these changes, this article revisits the question of the “pains” of electronic monitoring and its comparison to incarceration. I focus on three practices of electronic monitoring programs: home searches, communication monitoring, and long-term data storage to illustrate the ways in which the loss of autonomy, one of Sykes's original pains of imprisonment, is reproduced and remade. Rather than focusing on the aspects of programs that confine or limit the mobility of individuals, I draw on the tradition in carceral geography to consider how these practices recreate carcerality in new spaces and highlight the ways in which the experience of electronic monitoring is made carceral through the privacy intrusions and infringements to the self.